The finite element method : a practical course - Liu, G. R. (Gui-Rong); Quek, S. S. (Amsterdam : Butterworth-Heinemann, 2013)
Written for practicing engineers and students alike, this book emphasizes the role of finite element modeling and simulation in the engineering design process. It provides the necessary theories and techniques of the FEM in a concise and easy-to-understand format and applies the techniques to civil, mechanical, and aerospace problems. Updated throughout for current developments in FEM and FEM software, the book also includes case studies, diagrams, illustrations, and tables to help demonstrate the material. Plentiful diagrams, illustrations and tables demonstrate the materialCovers modeling techniques that predict how components will operate and tolerate loads, stresses and strains in realityFull set of PowerPoint presentation slides that illustrate and support the book, available on a companion website.
t t t t t t
engineering bookfair2015
Includes bibliographical references and index.
Keywords: Finite element method; Electronic books